Formulation and Evaluation of Capecitabine-Loaded Microsponges for Colon Targeting - Majumdar, Subhabrota; Dey, Sanjay; Mahanti, Beduin; Kar, Banhishikha; Nayak, Amit Kumar; Kar, Ayan Kumar (Current Drug Delivery, 2025)
<span class=
Keywords: microsponges